Data anxieties: Finding trust in everyday digital mess. Issue 1 (January 2018) - Pink, Sarah; Lanzeni, Debora; Horst, Heather
Digital data is an increasing and continual presence across the sites, activities and relationships of everyday life. In this article we explore what data presence means for the ways that the everyday is organised, sensed, and anticipated. While digital data studies have demonstrated how data is deeply entangled with the way in which everyday life is lived out and valued, at the same time our relationships with data are riddled with anxieties or small niggles or tricky trade-offs and their use is often chaotic and muddled, part of the inevitable uncertainty about what will happen next. If the presence of data is part of the environments we inhabit, this raises the question of how and why data is valuable to us and what forms of hope and trust enable this value to further develop.